2022
DOI: 10.3389/fped.2022.947059
|View full text |Cite
|
Sign up to set email alerts
|

Albumin level and progression of coronary artery lesions in Kawasaki disease: A retrospective cohort study

Abstract: BackgroundAlbumin (ALB) level is closely associated with the occurrence of intravenous immunoglobulin (IVIG) resistance and coronary artery lesions (CALs) in Kawasaki disease (KD). The association between ALB level and CALs progression, is critical to the prognosis of KD patients. But little is known about it. This study aims to investigate the effect of the ALB level on CALs progression in KD patients.MethodsA total of 3,479 KD patients from 1 January 2005 to 30 November 2020, in Wenzhou, China were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…At admission, our patient presented with risk factors for IVIg resistance and, consequently, coronary aneurysms, such as an age of <12 months, hypoalbuminemia, elevated liver enzymes, decreasing hemoglobin levels, and elevated CRP [24]. Hypoalbuminemia has been shown to be an independent risk factor for the occurrence and progression of CAAs [25].…”
Section: Discussionmentioning
confidence: 80%
“…At admission, our patient presented with risk factors for IVIg resistance and, consequently, coronary aneurysms, such as an age of <12 months, hypoalbuminemia, elevated liver enzymes, decreasing hemoglobin levels, and elevated CRP [24]. Hypoalbuminemia has been shown to be an independent risk factor for the occurrence and progression of CAAs [25].…”
Section: Discussionmentioning
confidence: 80%
“…Recent research has shown that ALB level in patients with cerebral infarction or coronary heart disease is significantly lower than in normal people, which has important predictive significance for the clinical treatment of IS and other cardiovascular and cerebrovascular diseases. 63,64 ALB can also effectively protect cerebral nerve cells. It not only improves blood flow but also protects brain cells, thereby promoting nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It can be clearly seen that ALB, AKT1, TNF, CASP3, EGFR, PTGS2, and MMP9 are important targets in the treatment of IS. Recent research has shown that ALB level in patients with cerebral infarction or coronary heart disease is significantly lower than in normal people, which has important predictive significance for the clinical treatment of IS and other cardiovascular and cerebrovascular diseases 63,64 . ALB can also effectively protect cerebral nerve cells.…”
Section: Discussionmentioning
confidence: 99%
“…The primary protein in plasma, albumin is primarily produced by hepatic parenchymal cells and serves as the clotting factor, substance binding, and colloid osmotic pressure regulator. 21 Albumin contains a sulfhydryl group that can control how inflammatory cells signal, limiting the release of inflammatory chemicals and functioning inadvertently as an antiinflammatory agent. This study discovered comparatively high albumin levels in persons with high TyG indices, which may be linked to increased synthesis as a result of higher TyG indices being associated with bigger waist circumference.…”
mentioning
confidence: 99%